Capsaicin induces ferroptosis via suppression of SLC7A11 activity and upregulation of ACSL4 mediated by AMPK in tongue squamous cell carcinoma - Zhao, Qiwei; Wang, Yu; Ding, Long; Li, Zhuang; Wang, Mengyang; Huang, Yueqing; Cao, Qiushi; Sun, Yaqin; Guo, Xiaohong (Frontiers in Oncology, 2025)
IntroductionThe global incidence of tongue squamous cell carcinoma (TSCC) has been steadily increasing. Our previous studies have demonstrated that capsaicin (CAP) promotes apoptosis and inhibits cell migration, thereby exerting anti-TSCC effects. In this study, we aimed to validate whether CAP induces ferroptosis in TSCC and to elucidate the underlying mechanisms.MethodsCell viability in HN6 and CAL27 cells was assessed using CCK-8 assays. Mitochondrial structural changes were observed via transmission electron microscopy (TEM). The levels of malondialdehyde (MDA), Fe2+, reactive oxygen species (ROS), and glutathione (GSH) were measured by the corresponding assay kits. Ferrostatin-1 (Fer-1) was utilized to confirm the involvement of ferroptosis. Western blotting was employed to evaluate the phosphorylation of AMP-activated protein kinase (AMPK), acyl-CoA synthetase long-chain family member 4 (ACSL4), and glutathione peroxidase 4 (GPX4). Additionally, Glutamic acid release was determined using an assay kit. The interaction between BECN1 and solute carrier family 7 member 11 (SLC7A11) was analyzed by co-immunoprecipitation (Co-IP). To elucidate the underlying mechanisms, lentiviral-mediated shRNA knockdown of AMPK was performed, with subsequent in vivo validation.ResultsCAP significantly suppressed the viability of HN6 and CAL27 cells. TEM analysis revealed mitochondrial damage following CAP treatment. Furthermore, CAP increased levels of MDA, Fe²⁺, and ROS while decreasing GSH; these alterations were reversed by Fer-1 treatment. Western blot analyses indicated that CAP upregulated phosphorylated AMPK and ACSL4 but downregulated GPX4 expression. Moreover, CAP inhibited glutamate release while enhancing BECN1-SLC7A11 binding, suggesting a reduction in SLC7A11 activity through the AMPK/BECN1 pathway. Notably, AMPK inhibition mitigated CAP-induced changes in p-BECN1, ACSL4, MDA, Fe²⁺, GSH, and ROS levels. In vivo experiments corroborated these findings.DiscussionOur study demonstrates that CAP activate the AMPK signaling, inhibits the activity of SLC7A11 and increases ACSL4 expression, thereby inducing ferroptosis in TSCC. These findings, supported by in vivo data, highlight CAP’s role in triggering ferroptosis as an anti-TSCC mechanism.